Influence of behavioral state, sex, and season on resource selection by jaguars (Panthera onca): Always on the prowl?. Issue 7 (10th July 2018) - Gese, Eric M.; Terletzky, Patricia A.; Cavalcanti, Sandra M. C.; Neale, Christopher M. U.
Abstract: How a predator uses its landscape to move through its territory and acquire prey is a fundamental question for scientific research. The influence of abiotic and biotic factors on space use of large carnivores has profound implications for their future management and conservation. In the Pantanal, Brazil, jaguars ( Panthera onca ) are the apex predator, but conflicts with cattle depredations pose a risk to their future conservation. We examined whether behavioral state, sex, and season influenced how jaguars used the landscape in the Pantanal. To accomplish this, we radio‐collared four females and six males; radio‐collared jaguars were monitored for 76 radio‐months with 11, 787 GPS locations acquired. We developed resource selection functions (RSFs) examining how female and male jaguars used their landscape during three behavioral states (moving, killing native prey, killing cattle) during two seasons (dry, wet). From the RSF models, we found similar variables and relationships of landscape characteristics that jaguars selected for when moving and when depredating native prey and cattle. While moving, jaguars selected for locations that were either in dense cover or very near dense cover, with higher plant diversity and closer to water than available across the landscape. While null models suggested jaguars opportunistically depredated native prey in the dry season and cattle in the wet season, there was some indication they selected for specific landscape characteristics, mainly dense cover when killing cattle in the dry season and native prey in the wet season. Both sexes killed native prey and cattle within dense cover or close to dense cover as expected of an ambush predator. Particular habitat types were not important as long as there was dense cover for concealment. Additionally, jaguars killed prey closer to water than was available on the landscape. The similar variables across the models showed the importance of dense cover and distance to dense cover during all three behavioral states indicating jaguars in the Pantanal were "always on the prowl." Understanding the spatial requirements for jaguars during the acquisition of native prey and cattle may lead to improved management strategies to allow for continued coexistence of jaguars in an area of traditional cattle production.